Biocementation for beach erosion control - Lim, Tricia Le Sing (Nanyang Technological University, 2025)
Beach erosion, accelerated by climate change-induced extreme storm events and rising sea levels, has become a pressing issue for coastal regions. Existing measures to combat erosion, such as the development of hard engineering structures and beach nourishment, while effective to a certain degree, often overlook the wider ecological impact. To encourage a response that considers the long-term well being of the coastal habitats, a novel approach by microbial induced calcium carbonate precipitation (MICP) using bioslurry has been proposed. This approach ensures environmentally sustainable stabilisation to be achieved in short durations. In this experimental study, several biocementation methods were assessed to identify sustainable solutions for beach erosion control. One-phase injection was conducted on beach sand extracted from East Coast Park, Singapore. The novel approach using bioslurry was subsequently carried out through model tests at varying chemical concentrations and bioslurry content to examine its potential in improving the mechanical properties of soil. Thereafter, an erosion control testing model integrating the bioslurry mixed sand was designed for practical implementation to enhance shoreline resilience. The findings indicated that bioslurry treated sand columns attained significant strength within a few days. For instance, the unconfined compression strength (UCS) for a treated column could reach up to 4.7 MPa within 3 days of treatment which cannot be replicated by traditional grouting methods. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) analyses revealed that the large rhombohedral-shaped crystals, also known as calcites, were contributing factors to the increased sample strength. Furthermore, the use of bioslurry mixed sand demonstrated negligible sediment erosion at upper sections of the slope. This emphasises the feasibility of employing bioslurry as a coastal protection measure against erosion.